TAQWA IN NEW NORMAL - Juhridin (Jurnal Sastra - Studi Ilmiah Sastra, 2020)
This research was written from the results of the compilation of secondary data that we obtained from various sources relating to Taqwa at the present time, as well as information from the mass media related to Islam in the New Normal situation.  Researchers hope, by reading this research can benefit us all, in this case can add to our insights about Taqwa in New Normal, faith and piety in modern life, especially for researchers. Indeed, this research is far from perfect, so the writer expects criticism and suggestions from readers forthe improvement towards a better direction